Pengelolaan Pendidikan Karakter Berbasis Peduli LingkunganDi SMP Negeri 6 Salatiga - Supriyadi, Agus; , Prof. Dr. Sutama, M.Pd; , Dr. Sumardi, M.Si (2015)
Low characters learners cause various problems that need to be handle with care. This study aims to describe the ways of (1) planning the management of care-based character education environment in the school; (2) organizing a school component, which is based on character education-based care for the environment; (3) implementation of care based character education environment for students in the school; (4) exercise control and evaluation of care based character education environment for students in the school. This research includes qualitative research with descriptive interpretative method. Research conducted at SMP 6 Salatiga with subjects of the study are principals, teachers, students and parents. Collecting data using interviews, observation and documentation. Data analysis techniques in this study using an interactive model with data reduction, data display, and data verification. Testing the validity of the data by using test of credibility through triangulation ofsources, discussion, and analysis of negative cases. The results showed that (1) school-based character education planning involving stakeholders as environmentally concerned having an interest , and disseminated to all people in schools; (2) the principal in organizing school component, which is based on character education-based care for the environment, applying the principle of an open strategy, creating a job description with clear tasks and functions, relationships vertically downwards, and mapping the various programs; (3) the implementation of eco-based character education in schools through learning programs (integrated), habituation, and self-development; (4) the efforts made to control and evaluate the activities of management of care-based character education environment with supervision and monitoring as well as evaluating the success rate of the program of activities.